Re-Evaluation of ELISA for the Detection of Bovine Tuberculosis and a New Proposal for Its Use in Eradication Efforts on Outbreak Farms - Chan-Ho Park; Jaemung Kim; Yun-Ho Jang; Sehyun Son; Sungweon Ryoo; Jung-Ho Kim; Sang-Min Won; Kyu-Wook Kim; Sungwon Hong; Bo-Young Jeon; Son-Il Pak; Byung-Il Yoon (Pathogens)
Bovine tuberculosis (bTB) is a zoonotic infectious disease and a chronic wasting illness. Accordingly, detecting and eradicating bTB remains a significant challenge in South Korea. This study evaluated the efficacy of a modified enzyme-linked immunosorbent assay (ELISA) protocol for detecting bTB in cattle. The protocol included two ELISA tests: one performed on the day of purified protein derivative (PPD) inoculation and another seven days post-inoculation. Results show a significant increase in ELISA detection rates, from 11% to 76%, particularly in cattle that tested positive for the tuberculin skin test (TST) and/or interferon-gamma (IFN-γ) assays (p < 0.0001). Notably, some cattle that were negative or had doubtful results in TST and IFN-γ assays transitioned to ELISA positive post-PPD inoculation. Additionally, some cattle identified as positive only by ELISA (S/p value ≥ 0.3) were confirmed to have bTB through gross examination or real-time reverse transcription polymerase chain reaction (rRT-PCR). The proposed protocol was validated in bTB outbreak farms using S/p thresholds of 0.3 (PPD inoculation day) and 0.5 (seven days post-PPD), enabling the detection of infected cattle missed by TST and IFN-γ assays. Implementing this approach successfully eradicated bTB in outbreak farms with minimal culling. These findings highlight the potential of incorporating sequential ELISA tests to enhance bTB detection and support eradication efforts.